2017
DOI: 10.3390/mi8110333
|View full text |Cite
|
Sign up to set email alerts
|

Light-Activated Metal Oxide Gas Sensors: A Review

Abstract: Conductometric gas sensors facilitated by photons have been investigated for decades. Light illumination may enhance device attributes including operational temperature, sensing sensitivity and selectivity. This paper aims to provide an overview on the progress of light-activated gas sensors, with a specific focus on sensors based on metal oxides. The material systems that have been studied include pure metal oxides, heterostructures of semiconductor-metal oxides and metal-metal oxides, and metal oxides with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 126 publications
3
53
0
Order By: Relevance
“…In this scenario, the use of UV light represents a promising route since UV light can induce gas desorption kinetics similar to what happens at high temperatures. Moreover, UV photons generate electron-hole pairs in ZnO, and the photo-induced carriers can interact with adsorbed gaseous species [7,9]. This can allow for the realization of gas sensors UV-activated at room temperature using ZnO nanostructures like nanosheets (hexagonal foils with thickness of about 100 nm and length of few micrometers), nanorods (parallelepipeds with a hexagonal base with a diameter greater than 50 nm and length of about 1.5 µm), and nano and microwires (cylindrical structures with length of about 10 µm and diameter of few nanometers and micrometers, respectively) [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the use of UV light represents a promising route since UV light can induce gas desorption kinetics similar to what happens at high temperatures. Moreover, UV photons generate electron-hole pairs in ZnO, and the photo-induced carriers can interact with adsorbed gaseous species [7,9]. This can allow for the realization of gas sensors UV-activated at room temperature using ZnO nanostructures like nanosheets (hexagonal foils with thickness of about 100 nm and length of few micrometers), nanorods (parallelepipeds with a hexagonal base with a diameter greater than 50 nm and length of about 1.5 µm), and nano and microwires (cylindrical structures with length of about 10 µm and diameter of few nanometers and micrometers, respectively) [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is of low cost, and Al-doped ZnO is of excellent conductivity as well as cheap, which is considered a superior substitute for the expensive indium tin oxide (ITO) transparent conductive material [14][15][16]. In addition, ZnO is found to be very sensitive to ultraviolet (UV) light, humidity, and gas and has been successfully applied in UV sensors [17], graphic imaging sensors [18], humidity sensors, and gas sensors [19,20]. Last but not least, it has been demonstrated that ZnO with bionic structure level holes is suitable for energy storage and utilization [21].…”
Section: Introductionmentioning
confidence: 99%
“…As for the preparation methods, various chemical-reaction-based approaches have been demonstrated to fabricate the nanostructured ZnO layer, such as chemical vapor deposition [13], spray pyrolysis [14], the sol-gel method [15], hydrothermal synthesis [16], etc., while fewer ZnO nanostructures have been demonstrated through the physical fabrication method. To further improve the sensing ability of ZnO, introducing heterojunction with other metal or metal oxide materials is also conventionally proposed [17,18]. For example, Shingange et al demonstrated that ZnO nanorods were functionalized with Au nanoparticles, yielding a high selectivity towards NH 3 compared with CO, CH 4 , and H 2 at the concentration of 100 ppm [8].…”
Section: Introductionmentioning
confidence: 99%